Nickel bioaccumulation as a predictor of toxicity - Leonard, Erin M. (My University, 2014)
Recently, the focus of metal toxicity has shifted from concentrations within the aqueous environment to bioaccumulation within the organism. In this regard, the Biotic Ligand Model (BLM) relates the binding of metal at specific toxic sites (“ligands”) to eventual toxicity, whereas the Tissue Residue Approach (TRA) relates metal burdens at whole body, tissue, or subcellular levels to eventual toxicity. However, much less is currently known regarding Ni in comparison to other metals. This thesis addresses this knowledge gap by evaluating the use of Ni bioaccumulation as a predictor of toxicity in a number of fish and invertebrate species; bioaccumulation endpoints examined included Michaelis-Menten uptake parameters (Kd, Bmax), a BLM parameter (log KNIBL values) and critical body residues (CBR50 values)
More sensitive species exhibited higher binding affinities and lower binding capacities for Ni. In invertebrates, a strong overall correlation was observed between log KNiBL values for whole organism binding and acute toxicity to the extent that measurement of toxicity was an acceptable alternative to measurement of binding affinity, and vice versa. However, in two teleosts, the same comparison showed that a Ni BLM built on bioaccumulation would be more protective than one built on toxicity. The results further validated a central concept of the BLM - that short term metal bioaccumulation is predictive of longer term toxicity. Acute (96-h) Ni bioaccumulation predicted chronic (15 or 30-day) mortality in both salt and fresh water. In the latter, acute (96-h) sub-cellular bioaccumulations of Ni in either biologically active (BAM) or biologically inactive metal pools (BIM) of one fish species (round goby) were also predictive of 30-d mortality. However, goby were more sensitive to Ni bioaccumulation in the BAM versus BIM fraction.
This thesis advances the use of bioaccumulation as a predictor of Ni toxicity and may have implications for metal toxicity frameworks such as the BLM and TRA.
Keywords: Nickel; bioaccumulation; toxicity; aquatic toxicology; invertebrates; teleosts; Biology; Other Physiology; Toxicology; Biology